PENDUGAAN CADANGAN KARBON DI TAMAN HUTAN RAYA INTEN DEWATA - Rian Susila; RIZKY NUR APRILIANI (Wanamukti: Jurnal Penelitian Kehutanan, 2019)
The existence of Tahura Inten Dewata have other functions as a Green Open Space in the process of reducing pollutants and climate stabilization. Vegetation has the ability to store carbon stocks, but the potential of Tahura Inten Dewata in storing carbon has not been studied. Object of research is carbon stock estimated in Tahura Inten Dewata. The method of research by storing it in wood density and biomass of tree which has a total area of ± 35.81 Ha. The results of these calculations will obtain the value of biomass, and carbon stocks represent 47% of the value of biomass. he total carbon stock in Tahura Inten Dewata is around 15,995.89 kg or 15,995 tons.